Hemophagocytic Lymphohistiocytosis During HIV Infection in Cayenne Hospital 2012–2015: First Think Histoplasmosis - Nguyen, Duc; Nacher, Mathieu; Epelboin, Loic; Melzani, Alessia; Demar, Magalie; Blanchet, Denis; Blaizot, Romain; Drak Alsibai, Kinan; Abboud, Philippe; Djossou, Félix; Couppié, Pierre; Adenis, Antoine (Frontiers in Cellular and Infection Microbiology, 2020)
Abstract Introduction Haemophagocytic Lymphohistiocytosis (HLH), during HIV infection is a rare complication with a poor prognosis. There are few data on HLH within the Amazon region. The objective was to describe epidemiological, clinical and therapeutic features of HIV-related HLH in French Guiana. Methods A retrospective analysis of adult HIV patients at Cayenne hospital with HLH between 2012 and 2015. A diagnosis of HLH was given if the patient presented at least 3 of 8 criteria of the HLH-2004 classification. Results. Fourteen cases of HLH were tallied during the study period. The mean age was 46 years with a sex ratio of 1.8. The most frequent etiology of HLH was an associated infection (12/14). Confirmed disseminated histoplasmosis, was found in 10 of 14 cases, and it was suspected in 2 other cases. The CD4 count was below 200/mm3 in 13/14 cases. An HIV viral load greater than 100 000 copies/ml was observed in 13/14 cases. An early treatment with liposomal amphotericin B was initiated in 12/14 cases. The outcome was favorable in 12/14 of all cases and in 10/12 cases involving histoplasmosis. Case fatality was 2/14 among all cases (14.3%) et 1/10 among confirmed disseminated histoplasmosis with HLH (10%). During the study period 1 in 5 cases of known HIV-associated disseminated histoplasmosis in French Guiana was HLH. Conclusion. Histoplasmosis was the most frequent etiology associated with HLH in HIV-infected patients in French Guiana. The prognosis of HLH remains severe. However, a probabilistic empirical first line treatment with liposomal amphotericin B seemed to have a favorable impact on patient survival.